A novel image authenticationand rightful ownership detection framework based on DWT watermarking in cloud environment - Khaleghparast, Reza (2013)
Cloud computing has been highlighted by many organizations because of its benefits to use it anywhere. Efficiency, Easy access information, quick deployment, and a huge reduce of cost of using it, are some of the cloud advantages. While cost reduction is one of the great benefits of cloud, privacy protection of the users‘ data is also a significant issue of the cloud that cloud providers have to consider about. This is a vital component of the cloud‘s critical infrastructure. Cloud users use this environment to enable numerous online transactions crossways a widespread range of sectors and to exchange information. Especially, misuse of the users‘ data and private information are some of the important problems of using cloud environment. Cloud untrustworthy environment is a good area for hackers to steal user‘s stored data by Phishing and Pharming techniques. Therefore, cloud vendors should utilize easy- to-use, secure, and efficient environment. Besides they should prepare a way to access cloud services that promote data privacy and ownership protection. The more data privacy and ownership protection in cloud environment, the more users will attract to use this environment to put their important private data. In this study, a rightful ownership detection framework has been proposed to mitigate the ownership protection in cloud environment. Best methods for data privacy protection such as image authentication methods, watermarking methods and cryptographic methods, for mitigating the ownership protection problem to use in cloud environment, have been explored. Finally, efficiency and reliability of the proposed framework have been evaluated and analyzed.